Visual graphic design analysis of the book Jingga Jenaka - Robbiya, Maiya Arsya; Kusumohendrarto, Raden Hadapiningrani (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
In this digital era, technology is making it increasingly convenient for people to engage in various activities, especially reading books. Many books are available in the form of e-books and can be easily accessed on mobile devices. However, physical books still dominate for those who enjoy the tangible experience of reading. In the book 'Jingga Jenaka,' simple stories are narrated in the form of poetry and comics, creating a harmonious narrative. The captivating visual elements that grab the reader's attention are intriguing to discuss in the context of the application of Visual Communication Design Theory. This analysis will delve into how the book 'Jingga Jenaka' aligns with Visual Communication Design Theory and whether its implementation is apt in conveying the author's emotions and sentiments to the readers.